The given radical expression is
![√(2-x)=x](https://img.qammunity.org/2019/formulas/mathematics/high-school/edtng29s8kahkx8tcsea63syf2qhnwlnqh.png)
Squaring on both the sides of the equation, we get
![2-x=x^(2)](https://img.qammunity.org/2019/formulas/mathematics/high-school/kflqx3pbz5zvkmpap70aj4l794t0xmsv21.png)
Bringing all the variables and constant to the right side of the expression, so we get:
![x^(2)+x-2=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/yktcvokftz78nuon8y322it5opi7aygjno.png)
By comparing the above expression with the standard form
![ax^(2)+bx+c=0](https://img.qammunity.org/2019/formulas/mathematics/college/hgh959w0zpi0uz7oj5g3wyaz2pvcosmn8z.png)
we get a=1, b=1 and c= -2
Discrimant(D) =
Discrimant(D)=
![(1)^(2)-4(1)(-2)](https://img.qammunity.org/2019/formulas/mathematics/high-school/kmd3wehldqb3rml22fenznoq34kmc131gz.png)
D=9
![x=(-b+√(D))/(2a) and x=(-b-√(D))/(2a)](https://img.qammunity.org/2019/formulas/mathematics/high-school/68htne4b52z1m0v1nziroa8cpvw0xvfbqq.png)
![x=(-1+√(9))/(2) and x=(-1-√(9))/(2)](https://img.qammunity.org/2019/formulas/mathematics/high-school/dsb2b289v7mgklmodfz8j41x9sy8t68zr2.png)
![x=(-1+3)/(2) and x=(-1-3)/(2)](https://img.qammunity.org/2019/formulas/mathematics/high-school/an1kgno744nfnpqfmkxjb5cfm6pwr3bscr.png)
x= -1 and 2 are the required solutions of the given radical expression.